A Year in the Social Life of a Teenager: Within-Persons Fluctuations in Stress, Phone Communication, and Anxiety and Depression. (September 2021) - Rodman, Alexandra M.; Vidal Bustamante, Constanza M.; Dennison, Meg J.; Flournoy, John C.; Coppersmith, Daniel D. L.; Nook, Erik C.; Worthington, Steven; Mair, Patrick; McLaughlin, Katie A.
Stressful life events (SLEs) are strongly associated with the emergence of adolescent anxiety and depression, but the underlying mechanisms remain poorly understood, especially at the within-persons level. We investigated how adolescent social communication (i.e., frequency of calls and texts) following SLEs relates to changes in internalizing symptoms in a multitimescale, intensive, year-long study ( N = 30; n = 355 monthly observations; n ≈ 5, 000 experience-sampling observations). Within-persons increases in SLEs were associated with receiving more calls than usual at both the month and moment levels and making more calls at the month level. Increased calls were prospectively associated with worsening internalizing symptoms at the month level only, suggesting that SLEs rapidly influence phone communication patterns, but these communication changes may have a more protracted, cumulative influence on internalizing symptoms. Finally, increased incoming calls prospectively mediated the association between SLEs and anxiety at the month level. We identify adolescent social communication fluctuations as a potential mechanism conferring risk for stress-related internalizing psychopathology.